Implementation of EVE-NG in Increasing the Effectiveness of Project-Based Learning in the Network Computer Engineering Technology Study Program - Utomo, Hendrik Setyo; Sholeha, Eka Wahyu; Supriyanto, Arif; Rusmana, Deni; Majid, Al (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The increasing demand for practical skills in computer networks has made hands-on learning a crucial element in information technology education. This study focuses on evaluating the usability of EVE-NG, a network simulation platform, to optimize project-based learning for students in the Computer Engineering and Network Program (TRKJ) at Politeknik Negeri Tanah Laut. The students, in their third semester, were selected as respondents, as they were enrolled in the Computer Networks 3 course, which is relevant to the practical use of EVE-NG. A usability analysis was conducted using five key indicators: Learnability, Memorability, Efficiency, Errors, and Satisfaction, assessed through questionnaires. The findings revealed that EVE-NG performs adequately across all indicators, with average scores ranging from 2.82 to 3.04, indicating good usability overall. Learnability and Memorability were rated as